Development of a React Native-Based Mobile E-Commerce Application to Optimize Online Sales for MSMEs: A Case Study of New Delisio Bakery Cake - Suryanto, William Kessler; Sancoko, Sulistyo Dwi (JISA(Jurnal Informatika dan Sains), 2024)
The development of a mobile-based e-commerce application aims to assist MSMEs, particularly New Delisio Bakery Cake, in optimizing their online sales and expanding market reach. Currently, New Delisio operates using conventional methods that limit its customer base and overall sales potential. To address this challenge, the application was developed following the waterfall methodology, encompassing requirements analysis, design, implementation, testing, and deployment. The front-end was built using React Native, while the back-end utilized Express.js and MongoDB. A user testing phase was conducted with a sample group, providing valuable feedback on usability and functionality. The application offers a user-friendly platform for customers to browse and purchase products, while enabling the business to efficiently manage operations. The test results showed a high overall success rate of 92.52%, with 91.11% success for user interactions and 100% for admin tasks. This demonstrates the application's effectiveness in enhancing usability and functionality. By leveraging modern mobile technology, the solution enhances the store's visibility, engagement, and scalability, potentially increasing revenue. This research demonstrates the potential for MSMEs to transition into the digital market through a structured development process and iterative improvements.